Safety and Blood Pressure Outcomes of Renal Denervation for Resistant Hypertension: Meta-Analysis of Randomized Trials - Mahmood, Arhum; Aboelmaaty, Mohamed; Virk, Ghazala S.; Khan, Sumaiya; Hanan, Abdul; Saeed, Zain Bin; Ahmed, Sara Zubair; Sohaib, Muhammad Ahmer; Iqbal, Ahmad Sheraz; Essani, Binish; et al. (Cardiology and Cardiovascular Medicine, 2025)
Background: Catheter-based renal denervation (RDN) is a potential nonpharmacological treatment for resistant hypertension, though its efficacy and safety require further validation. This meta-analysis compared RDN to sham procedures on blood pressure (BP) outcomes and safety. Methods: We pooled data from 6 randomized controlled trials (999 patients) using random-effects models. Primary outcomes were changes in 24-hour ambulatory systolic/diastolic BP (SBP/DBP) and office SBP. Safety assessed adverse events and renal function. Heterogeneity was evaluated via I². Results: RDN significantly reduced 24-hour ambulatory DBP (SMD: -0.23; 95% CI: -0.47, -0.00; p=0.05) and office SBP (SMD: -0.29; 95% CI: -0.50, -0.08; p=0.007) versus sham. The reduction in 24-hour ambulatory SBP was not significant (SMD: -0.21; 95% CI: -0.47, 0.05; p=0.11). Adverse event rates and renal function changes were similar between groups (p=0.86). Analyses showed moderate-to-high heterogeneity (I²=62%-69%). Conclusions: RDN effectively lowers ambulatory DBP and office SBP with a favorable safety profile. Its effect on ambulatory SBP remains uncertain. While a promising option for resistant hypertension, standardized protocols and long-term data are needed to confirm efficacy and durability.